Social Factors in Celebrity Suicides: A Content Analysis of South Indian Online News Reports - Tom, Leya Anna; Syed, Haniya Zehra; Kabir, Russell (Asian Journal of Psychiatry and Mental Health, 2024)
Background: The reasons for celebrity suicide are multifaceted and often involve a complex interplay of mental health challenges, intense public scrutiny, and the pressures associated with fame—this content analysis aimed to explore the social factors contributing to celebrity suicides in South India. By examining the prevalence of specific factors, the research seeks to provide valuable insights into the dynamics of these tragic incidents. Methods: In this content analysis study, five leading Indian online news portals (i.e. Times of India, Indian Express, India Today, NDTV, and the Week) were meticulously chosen for a retrospective analysis. The focus was on English-language news. The study incorporated variables such as age, place of suicide, suicide date, reasons for suicide, and other identifying factors to establish patterns. After eliminating repetitions, a final dataset of 17 unique reports was assessment. Results: The findings underscored the complex interplay of demographic, contextual, and societal factors contributing to celebrity suicides. The study identified the significant influence of specific news portals, prompting contemplation on media's potential impact on public perception. Utilizing a word cloud approach, the research has elucidated contributing factors such as depression, love failure, financial problems, mental health issues, relationship challenges, despair, and deprived opportunities. Conclusion: This frequency content analysis offers valuable insights into the social factors of celebrity suicides in South India, providing a foundation for further research and collaborative efforts. Addressing mental health challenges within this population necessitates a holistic approach, encompassing media responsibility and targeted interventions.